Menggali Metode Pendidikan Islam dalam Al-Quran: Studi al-Quran Surat an-Nahl/16: 125 - Ade Eka Pradana (Matan : Journal of Islam and Muslim Society, 2022)
Islamic education from the time of Rosulullah SAW. to the present day has had a very rapid development, in the world of education many teachers or educational scientists have contributed in the form of discovering Islamic education methods for the advancement of the Islamic generation. But in fact there are still many methods that can only teach material but do not have a direct impact on character education of a child. Here the authors remind that in Islamic education Allah SWT has provided a perfect method in the Qur'an surah An-Nahl verse 125 as a guide for teachers to use this method which affects the heart, mind and behavior of a child. In the Qur'an Surah An-Nahl verse 125, there are three methods taught by Allah SWT to us educators or preachers, namely teaching Islam with bills of wisdom, mauizhal hasanah and discussion. In various methods such as lectures, exemplary examples and other methods are actually inseparable from the three methods contained in Surah An-Nahl verse 125. So here the author explains about the method of Islamic Education in the Qur'an Surat An-Nahl verse 125. The author hopes that with an explanation These educators and preachers adhere to the da'wah method taught by Allah SWT in Surat An-Nahl verse 125 for success in educating the Islamic generation and using various methods or collaborating several methods for success in Islamic Education.